2021
DOI: 10.1530/raf-20-0073
|View full text |Cite
|
Sign up to set email alerts
|

Maternal protein restriction affects fetal ovary development in sheep

Abstract: Maternal malnutrition has important developmental consequences for the fetus. Indeed, adverse fetal ovarian development could have lifelong impact, with potentially reduced ovarian reserve and fertility of the offspring. This study investigated the effect of maternal protein restriction on germ cell and blood vessel development in the fetal sheep ovary. Ewes were fed control (n=7) or low protein (n=8) diets (17.0g versus 8.7g crude protein.MJ-1 metabolizable energy) from conception to day 65 of gestation (g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 34 publications
(62 reference statements)
0
8
0
Order By: Relevance
“…Studies in animal models have suggested that maternal undernutrition results in a smaller ovary in the fetus and an increased testosterone concentration [ 83 , 84 ]. In addition, protein restriction in mothers has been shown to impair germ cell and blood vessel development in the fetal ovaries of sheep and the number of primordial follicles in mice [ 85 , 86 ]. The second study also found that primordial follicles were significantly depleted by 37% at PN21 and 51% at 24-week mice with statistical significance.…”
Section: Hormonal Influence On Ovarian Reservementioning
confidence: 99%
“…Studies in animal models have suggested that maternal undernutrition results in a smaller ovary in the fetus and an increased testosterone concentration [ 83 , 84 ]. In addition, protein restriction in mothers has been shown to impair germ cell and blood vessel development in the fetal ovaries of sheep and the number of primordial follicles in mice [ 85 , 86 ]. The second study also found that primordial follicles were significantly depleted by 37% at PN21 and 51% at 24-week mice with statistical significance.…”
Section: Hormonal Influence On Ovarian Reservementioning
confidence: 99%
“…In recent years, the important role of locally produced mediators (paracrine actions) such as growth factors, cytokines and various peptides in modulating folliculogenesis and ovulation has been established (Hunter et al, 2004; Mishra et al, 2017; Nwachukwu et al, 2023; Rawlings et al, 2003; Scaramuzzi et al, 2011; Schams et al, 2009). During the ovulation process, the LH peak stimulates molecular mechanisms and different locally produced factors, which support the effect of gonadotropins in the completion of the ovulation process and the formation of the CL (Berisha & Schams, 2005; Juengel et al, 2021).…”
Section: Ovarian Cycle In Ruminantsmentioning
confidence: 99%
“…Growth factors like IGF system members can stimulate either the proliferation or the differentiation and differentiated functions of granulosa cells, depending on the follicle's development stage (Scaramuzzi et al, 2011). While the last publication of Nwachukwu et al (2023) highlights the importance of IGF signalling in regulating luteal angiogenesis and function in the cow. In addition, some research groups have demonstrated the importance of adipokines system members like adiponectin, resistin, chemerin, visfatin and apelin in the regulation of bovine ovarian function (Juengel et al, 2021; Kurowska et al, 2021; Thaqi et al, 2023).…”
Section: Ovarian Cycle In Ruminantsmentioning
confidence: 99%
See 1 more Smart Citation
“…Another study reported that primordial follicles from fetal sheep ovaries collected on day 135 of gestation following a 60% nutrient restriction from day 50 of gestation onwards had a decreased cellular proliferation rate compared with those from fetal ovaries of adequately fed ewes [ 89 ]. Nwachukwu et al [ 90 ] fed ewes low protein diets for the first half of gestation. Ovarian weight in the fetuses was again reduced compared with the controls, but in this case there were no apparent differences in germ cell development at mid gestation.…”
Section: Influence Of Fetal Programming On the Development Of Specifi...mentioning
confidence: 99%